2021
DOI: 10.1128/mra.00753-21
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Bacillus amyloliquefaciens EA19, an Endophytic Bacterium with Biocontrol Potential Isolated from Erigeron annuus

Abstract: Bacillus amyloliquefaciens strain EA19 is an endophyte isolated from Erigeron annuus with antifungal activity against Blumeria graminis f. sp. tritici , Magnaporthe oryzae , and Fusarium graminearum . The genome sequence of this strain is 3.96 Mb and contains 3,421 coding sequences, which will facilitate an understanding of the mechanisms of biocontrol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Varying CAZyme profiles of intestinal microbes may had different capabilities of carbohydrate metabolism [42]. Comparison of CAZyme genes in five B. amyloliquefaciens strains, including TL106, HK1, EA19, LL3 and XH7 revealed that B. amyloliquefaciens TL106 had more types of CAZymes genes than the other four strains [43][44][45][46]. GH genes were took a large part in the genome of B. amyloliquefaciens, consistent with those of the genome of Aspergillus fumigatus Z5, which showed highly efficient cellulose-degradation capability [47].…”
Section: Discussionmentioning
confidence: 99%
“…Varying CAZyme profiles of intestinal microbes may had different capabilities of carbohydrate metabolism [42]. Comparison of CAZyme genes in five B. amyloliquefaciens strains, including TL106, HK1, EA19, LL3 and XH7 revealed that B. amyloliquefaciens TL106 had more types of CAZymes genes than the other four strains [43][44][45][46]. GH genes were took a large part in the genome of B. amyloliquefaciens, consistent with those of the genome of Aspergillus fumigatus Z5, which showed highly efficient cellulose-degradation capability [47].…”
Section: Discussionmentioning
confidence: 99%